Increased incidence of cervical cytological abnormalities in women with genital warts or contact with genital warts: a need for increased vigilance?. Issue 6 (December 1991) - Rowen, D; Carne, C A; Sonnex, C; Cooper, P
Abstract : OBJECTIVE--To determine whether women who have a history of genital warts or whose sexual partners have such a history were more likely to have borderline or dyskaryotic cervical smears than other women. DESIGN--Prospective study conducted over a five month period. SETTING--A genitourinary medicine clinic in Cambridge, UK. PATIENTS--One hundred and eighty five women who attended the clinic during the study period, on whom cervical cytology was performed. Ninety-seven had a history of genital warts and twenty had partners with genital warts. METHODS--Cervical cytology taken by standard methods. Demographic data and sexual history obtained by questionnaire. Colposcopy was performed on patients with a history of warts or wart contact. OUTCOME MEASURED--Relative incidence of cytological abnormalities in the various groups of patients. RESULTS--"Borderline" nuclear change was the most frequent abnormality reported in the wart contact group (six cases) whereas mild dyskaryosis was the most frequent abnormal finding in those women with a history of warts (21 cases). CONCLUSIONS--Women with warts or contact with genital warts were more likely to have borderline or dyskaryotic cervical smears than women without such a history. Recommendations for follow-up of these patients are made.